PENDIDIKAN AGAMA ISLAM DALAM PERSIMPANGAN - Mujib Ridlwan (LPPM Institut Agama Islam Al-Hikmah Tuban, 2011)
Islamic religious education in schools today can be said to be still far from a perfect score, presence of religious education in public schools is a long struggle the fighters of this country to include religious education in schools, because of previous religious education in schools does not exist, to be there, and eventually became important because it is based on the desire to form the character of students. But so far is still far from expectations with a variety of evidence amoral actions and crimes committed students.As an alternative to answering the 'failure' of religious education in schools. Now, there are many full days school programs, the concept essentially adopted the concept of boarding school education. Community and parents have realized that the real, proven, full day school preferred by many people. But unfortunately, the full day until now has not been able to enjoy all the circles, because of high cost. Full day school that tries to answer the weakness of religious education which has been implemented in public schools can only be enjoyed by children of rich parents.